Un/doing Ethnicity im öffentlichen Dienst Ethnografien zum ethnischen Differenzieren am Beispiel von Jugendamt und Polizei - Piñeiro, Esteban (Social Cohesion and Cultural Pluralism, 2021)
"How does public administration deal with a population that it perceives as diverse? Which ethnic differentiations are either produced by everyday concrete administra-tive actions or blurred in the sense of undoing ethnicity? Two intervening street-level bureaucracies are examined, a municipal youth welfare office and the police of a medium-sized town. The focus is on the close intertwining of ethnicizations with social work and with police categorizations and work practices. Ethnic attributions in social work and in police work can come into play when they are considered purposeful, opportune, helpful or effective in everyday work. At first glance, the official approach to ethnicity appears ambivalent and diffuse, and the intervention of the youth welfare office and the police in this regard appears intrans-parent and unpredictable. However, emphasizing or overlooking ethnic differences follows an instrumental logic, which can ultimately lead to the concealment or rein-forcement of state intervention. "